2021
DOI: 10.3390/cells10071609
|View full text |Cite
|
Sign up to set email alerts
|

RelB and Neuroinflammation

Abstract: Neuroinflammation within the central nervous system involves multiple cell types that coordinate their responses by secreting and responding to a plethora of inflammatory mediators. These factors activate multiple signaling cascades to orchestrate initial inflammatory response and subsequent resolution. Activation of NF-κB pathways in several cell types is critical during neuroinflammation. In contrast to the well-studied role of p65 NF-κB during neuroinflammation, the mechanisms of RelB activation in specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 236 publications
(333 reference statements)
0
13
0
Order By: Relevance
“…In fact, TNF was the most up-regulated gene, with a 104-fold increase, followed by TNF-c (Lymphotoxin beta, LTB), with a 32.8-fold change ( Figure 3 , Table 1 ). Interestingly, LTB is a known inducer of the noncanonical NFκB inflammatory pathway [ 54 ] and was found to be up-regulated both at 6 and 24 h in SARS-CoV-2-exposed HBMEC by RT-qPCR ( Figure 3 E). Although our RNA-Seq data revealed an increase in NFκB2 (p100/p52) and NFκBIA (IκBα), we performed RT-qPCRs with additional biological samples for NF-κB1 (p105/p50) and NF-κB2 and observed that due to biological variability such genes remained unaltered in challenged cultures ( Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, TNF was the most up-regulated gene, with a 104-fold increase, followed by TNF-c (Lymphotoxin beta, LTB), with a 32.8-fold change ( Figure 3 , Table 1 ). Interestingly, LTB is a known inducer of the noncanonical NFκB inflammatory pathway [ 54 ] and was found to be up-regulated both at 6 and 24 h in SARS-CoV-2-exposed HBMEC by RT-qPCR ( Figure 3 E). Although our RNA-Seq data revealed an increase in NFκB2 (p100/p52) and NFκBIA (IκBα), we performed RT-qPCRs with additional biological samples for NF-κB1 (p105/p50) and NF-κB2 and observed that due to biological variability such genes remained unaltered in challenged cultures ( Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…Although our RNA-Seq data revealed an increase in NFκB2 (p100/p52) and NFκBIA (IκBα), we performed RT-qPCRs with additional biological samples for NF-κB1 (p105/p50) and NF-κB2 and observed that, due to biological variability, such genes remained unaltered in infected cultures ( Figure 3D ). However, RELB, the main activator of noncanonical NF-κB signaling pathway (Mockenhaupt et al, 2021), was shown to be up-regulated by confirmatory RT-qPCR at 24 hpi ( Figure 4 ). We also further confirmed by RT-qPCR the up-regulation of inflammation-related genes, including LTB, TNF, IL-6, CXCL1, CXCL2 and CXCL8 ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 86%
“…In fact, TNF was the most up-regulated gene, with 104-fold increase, followed by TNF-c (Lymphotoxin beta, LTB), with 32.8-fold change ( Figure 3, Table 1 ). Interestingly, LTB is a known inducer of noncanonical NFκB inflammatory pathway (Mockenhaupt et al, 2021) and was found to be up-regulated both at 6 and 24 hpi in SARS-CoV-2 infected HBMEC by RT-qPCR ( Figure 3E ). Although our RNA-Seq data revealed an increase in NFκB2 (p100/p52) and NFκBIA (IκBα), we performed RT-qPCRs with additional biological samples for NF-κB1 (p105/p50) and NF-κB2 and observed that, due to biological variability, such genes remained unaltered in infected cultures ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance trends of TLR-4 and NF-κB are not consistent, which may be derived from various triggers of the canonical NF-κB pathway. In addition to cell surface receptors such as toll-like receptors (TLRs), proinflammatory cytokines and T cell receptors or B cell receptors can trigger NF-κB pathway as well ( 41 , 42 ). In addition, GAFP levels and pro-inflammatory cytokine IL-1β secretion increased after AQP2 overexpression.…”
Section: Discussionmentioning
confidence: 99%